Nietzsche's Criticism of logic - Alaa alddin, Ghassan (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
During the course of its long history, the science of logic has been massively shaken by a variety of interpretations and reviews. Besides, it has undergone immense criticisms, which led its pioneers to reconsider the nature of the principles and bases on which this science is established, Thus relieving the burden and negativity of such criticism. In this context, Friedrich Nietzsche's criticism of logic is almost one of the most outstanding and profound manifestations of that science, Which created a fertile ground from which the latter philosophers, who followed the criticism founded and nourished by Nietzsche, emerged. Hence, in this research, we try to shed light on the nature of Nietzschean criticism of logic by digging deep into the texts and deconstructing them for the purpose of uncovering the justifications of this criticism, and identifying the contexts of knowledge from which Nietzsche has begun his deep philosophical practice of that criticism.